STIGMATISATION OF MENTALLY ILL PEOPLE AND THEIR DESTIGMATISATION: SOCIAL-PSYCHOLOGICAL DIMENSION - I B Bovina; A V Yakushenko (Peoples' Friendship University of Russia (RUDN University), 2015)
The stigmatisation of mentally ill people is discussed in the article; the social representations theory is seen as one of the most productive among the different models of stigmatisation. The strategies of destigmatisation are also discussed in the article.